Advances in Chemical Vapor Deposition - Vernardou, Dimitra (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Pursuing a scalable production methodology for materials and advancing it from the laboratory to industry is beneficial to novel daily-life applications. From this perspective, chemical vapor deposition (CVD) offers a compromise between efficiency, controllability, tunability and excellent run-to-run repeatability in the coverage of monolayers on substrates. Hence, CVD meets all of the requirements for industrialization in basically all areas, including polymer coatings, metals, water-filtration systems, solar cells and so on. The Special Issue "Advances in Chemical Vapor Deposition" is dedicated to providing an overview of the latest experimental findings and identifying the growth parameters and characteristics of perovskites, TiO2, Al2O3, VO2 and V2O5 with desired qualities for potentially useful devices.